Spirinia lara sp. n. and Spirinia sophia sp. n. (Nematoda, Desmodoridae) from the Brazilian continental margin (Campos Basin, Rio de Janeiro) - Da Silva, Maria Cristina; de Castro, Francisco José Victor; Da Fonseca Cavalcanti, Mariana; Da Fonsêca-Genevois, Verônica (Zootaxa, 2009)
In deep-sea sediments from Campos Basin two new species of Spirinia were found. Spirinia lara sp. n. is mainly characterized by the presence of paired somatic papillae linked to gland cells and distributed all over the body while Spirinia sophia sp. n. possesses an irregular distribution of these glandular somatic papillae.